2022
DOI: 10.3390/met12050737
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Beam Power on Structures and Mechanical Characteristics of Electron-Beam-Welded Joints of Copper and Stainless Steel

Abstract: In this study, we present the results of electron-beam welding of joints with 304-L stainless steel and copper. The influence of the beam’s power on the structures and mechanical properties of the welded joints was studied; the experiments were realized at a beam deflection of 0.3 mm to the Cu plate and beam powers of 2400, 3000, and 3600 W. The phase compositions of the obtained welded joints were studied by using X-ray diffraction (XRD); the microstructure and chemical composition were investigated by scanni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…For this reason, the plates were preheated to a temperature of 200 • C. Another important factor that was necessary for the formation of a strong joint is the offset of the beam toward the aluminum alloy [29]. Our previous studies [30] demonstrated that shifting the electron beam toward the metal with lower melting temperature results in the formation of a higher integrity weld.…”
Section: Methodsmentioning
confidence: 99%
“…For this reason, the plates were preheated to a temperature of 200 • C. Another important factor that was necessary for the formation of a strong joint is the offset of the beam toward the aluminum alloy [29]. Our previous studies [30] demonstrated that shifting the electron beam toward the metal with lower melting temperature results in the formation of a higher integrity weld.…”
Section: Methodsmentioning
confidence: 99%
“…Obtaining a strong joint between titanium and aluminum alloy is a difficult task due to the different thermophysical characteristics of the two materials [3]. Electron beam welding (EBW) is a suitable technology for fabrication of joint between dissimilar materials [4][5][6][7][8]. This method allows the formation of deep welded joints with very high degree of purity.…”
Section: Introductionmentioning
confidence: 99%
“…This process can occur with or without the use of filler material, with continuity in the nature of the material of the parts. Welding copper alloys can be carried out using various methods, such as laser, electron beam, resistance, friction, ultrasonic, electromagnetic pulse, and brazing [13][14][15][16]. Brazing is a process of joining materials that occur through the melting and solidification of a filler metal that is placed in contact with the base material, that is, with the components to be welded, resulting in a watertight and tight joint in a structural connection between the pieces.…”
Section: Introductionmentioning
confidence: 99%